The Influence Of Good Corporate Governance to Financial Report - Anita Wijayanti, Muh. Yulian Ibnu Zulham, Suhendro & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study is aim to examine and analyze the influence of good corporategovernance to financial report. Using managerial ownership, institusionalownership, independent commisioner, audit committee and board size company asgood corporate governanceâs instrument and cash flow return on asset (CFROA) asfinancial reportâs performance. Sample of this report was financial report or annualreport from pharmacy company that listed in Indonesia stock exchange during2011-2016. The result of this studyshows that managerial ownership, institutionalownership and independent commisioner significanly influence financialperformance it can be seen form the ttest result for each independent variable ishigher than ttabel, which is mean the hypothesis were accepted. Yet audit committeeand board size company are not significanly influence financial performance. Itseen by the ttest result that the value of the ttest is lower than ttable value.Keyword : good corporate governance, financial performance